Oxidation of α,β-Unsaturated Alcohols by Nicotinium Dichromate: A Kinetic Study - SEKAR, K.G. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of α, β-unsaturated alcohols by nicotinium dichromate (NDC), have been studied in 50% acetic acid-water medium. The reaction is first order each in the concentration of oxidant and substrate Increase in acidity increases the rate of the reaction. Increase in ionic strength has appreciable effect on the reaction rate. The rate of the reaction decreases with increase in the dielectric constant of the medium. The reaction does not induce the polymerization of acrylonitrile. The retardation of the rate by the addition of Mn2+ ions confirms that a two electron transfer process is involved in the reaction. The reaction rates have been determined at different temperatures and the activation parameters calculated and a suitable mechanism has been proposed. The order of reactivity is allyl alcohol < crotyl alcohol < cinnamyl alcohol.